Transparent and Highly Flexible Hierarchically Structured Polydimethylsiloxane Surfaces Suppress Bacterial Attachment and Thrombosis Under Static and Dynamic Conditions. Issue 15 (28th February 2022) - Khan, Shadman; Jarad, Noor Abu; Ladouceur, Liane; Rachwalski, Kenneth; Bot, Veronica; Shakeri, Amid; Maclachlan, Roderick; Sakib, Sadman; Weitz, Jeffrey I.; Brown, Eric D.; Soleymani, Leyla; Didar, Tohid F.
Abstract: The surface fouling of biomedical devices has been an ongoing issue in healthcare. Bacterial and blood adhesion in particular, severely impede the performance of such tools, leading to poor patient outcomes. Various structural and chemical modifications have been shown to reduce fouling, but all existing strategies lack the combination of physical, chemical, and economic traits necessary for widespread use. Herein, a lubricant infused, hierarchically micro‐ and nanostructured polydimethylsiloxane surface is presented. The surface is easy to produce and exhibits the high flexibility and optical transparency necessary for incorporation into various biomedical tools. Tests involving two clinically relevant, priority pathogens show up to a 98.5% reduction in the biofilm formation of methicillin‐resistant Staphylococcus aureus and Pseudomonas aeruginosa . With blood, the surface reduces staining by 95% and suppresses thrombin generation to background levels. Furthermore, the surface shows applicability within applications such as catheters, extracorporeal circuits, and microfluidic devices, through its effectiveness in dynamic conditions. The perfusion of bacterial media shows up to 96.5% reduction in bacterial adhesion. Similarly, a 95.8% reduction in fibrin networks is observed following whole blood perfusion. This substrate stands to hold high applicability within biomedical systems as a means to prevent fouling, thus improving performance. Abstract : A transparent, highly flexible polymeric substrate is developed. The substrate uses a combination of hierarchical structuring and lubricant infusion to demonstrate strong bacterial repellency and antithrombotic properties in both static and dynamic conditions. The substrate shows potential for use within in vivo biomedical devices.